DETERMINAN PENGUNGKAPAN ASET BIOLOGIS PADA PERUSAHAAN SEKTOR AGRIKULTUR DI BEI PERIODE 2018- 2021 - Pangestu, Juan Carlos; Aprilliani, Jessica; Marbella, Lica (Owner : Riset dan Jurnal Akuntansi, 2024)
Agricultural sector companies are unique for their agricultural activities so that the emergence of biological assets. These biological assets certainly have different characteristics compared to other assets because there is a possibility of adding or reducing the value of these assets due to biological factors in them. Changes in biological assets can have an impact on investors' assessment of company performance and value. This study aims to examine the effect of biological asset intensity, audit committee meetings, company size, KAP type and ROA on the disclosure of biological assets in agricultural sector companies listed on the Indonesia Stock Exchange in 2018-2021. Sampling was done by purposive sampling technique. This type of research uses descriptive statistical tests and multiple linear regression methods. The objects in this study are the financial reports of agricultural sector companies listed on the IDX from the 2018 -2021 period. The results showed that the intensity of biological assets has an influence on the disclosure of biological assets but other independent variables have no significant effect.